Language Forms of Rejection in Student-Student and Student-Lecturer Interactions in the Department of Javanese Language and Literature UNNES: A Sociolinguistic Study - Nurzanah, Messi; Utomo, Tri Duto (Abjad Journal of Humanities & Education, 2023)
This research aims to reveal the forms of language of rejection used by students and in interactions with lecturers at the Department of Javanese Language and Literature (Bahasa dan Sastra Jawa/BSJ), UNNES. A sociolinguistic study approach is used to explore this phenomenon's social and linguistic context. This research used descriptive qualitative research. The research results show that students in this context use various forms of rejection language explicitly and implicitly as a form of attitude or response to certain situations. The analysis also revealed differences in the use of rejection language between interactions between fellow students and interactions with lecturers. Social factors, culture, and academic hierarchy can influence the choice of rejection language used.